Measurement of Gauge Block Surface Structure Using 12-Lamp Photometric Stereo Method - Syahwir, Irawati Dewi; Setiawan, Irwan; Khairah, Inayah Dwi (Program Studi Teknik Komputer, 2026)
Purpose – This study aims to develop and evaluate a non-contact method for measuring surface roughness of gauge blocks using an enhanced photometric stereo approach with multiple lighting sources, as an alternative to conventional coordinate measuring machine (CMM) methods that may damage the surface. Design/methods/approach – The research employs a photometric stereo method using 12 different lighting sources arranged at 55° intervals. The captured images are reconstructed using a photometric stereo algorithm to generate a three-dimensional surface model. Surface roughness is determined by measuring peak and valley heights and calculating their average. The objects tested are gauge blocks of class 0 and class 1, compared against standard blocks based on ISO/R 468-1966. Findings – The results show that gauge blocks of class 0 and class 1 have roughness values close to the N7 standard group, with an average roughness of 1.6 μm. The reconstruction results indicate an average error of 0.11933 μm for N7 blocks and -0.0718 μm for N8 blocks. The photometric stereo method demonstrates lower error compared to conventional contact-based measurements. Research implications/limitations – This method provides a promising non-contact alternative for surface roughness measurement and calibration. However, the study is limited to specific lighting configurations and gauge block samples, and further research is needed to validate its application across different materials and surface conditions. Originality/value – This study introduces an improved photometric stereo configuration using 12 lighting sources, enhancing reconstruction accuracy and offering a safer and more precise alternative for surface roughness measurement, particularly for calibration processes regulated by the National Standardisation Agency.